Allogeneic hematopoietic stem cell transplantation for patients with relapsed/refractory systemic anaplastic large cell lymphoma: a retrospective analysis of the Lymphoma Working Party of the European Society for Blood and Marrow Transplantation - Domingo-Domènech, Eva; Boumendil, A.; Climent, F.; Socié, G.; Kroschinsky, F.; Finel, H.; Vandenbergue, E.; Nemet, D.; Stelljes, M.; Bittenbring, J. T.; Robinson, S.; Montoto, S.; et al. (Bone marrow transplantation, 2020)
Information regarding the curative role of allogeneic stem cell transplantation (allo-HCT) in systemic anaplastic large cell lymphoma (sALCL) is scarce. We analyzed the results of allo-HCT in patients with relapsed/refractory sALCL with special emphasis on the role of brentuximab vedotin (BV) as a bridge to allo-HCT. Forty-four patients (24 females, median age 38 years) with sALCL were included. Twenty-three patients (52%) received BV before allo-HCT; BV-treated patients were more heavily pretreated (≥3 lines of therapy in 74% vs. 38%, p = 0.04). Twenty-three patients (52%) were in complete remission (CR) at allo-HCT. Three-year nonrelapse mortality and incidence of relapse (IR) after allo-HCT were 7% and 40%, respectively. With a median follow-up of 39 (12-69) months for survivors, 3-year progression-free survival (PFS) and overall survival were 53% and 74%, respectively. Univariate analysis showed that heavily pretreated patients and those not in CR had a higher IR and a lower PFS. The use of BV before transplant did not impact on any of the outcomes. Allo-HCT is a curative therapeutic strategy in a significant proportion of patients with relapsed/refractory sALCL; BV does not seem to modify transplant-related outcomes but might be able to render more patients candidates for this curative treatment.
Published online: 6 November 2019
Gesehen am 16.04.2020